Effects of 6-dimethylaminopurine, cytochalasin B and cycloheximide on in vitro development of I pig cloned embryos - Van, Nguyen Khanh; Huu, Quan Xuan; Huong, Vu Thi Thu; Lan, Pham Doan (Vietnam Journal of Biotechnology, 2020)
The present study was conducted to evaluate the effects of 6-dimethylaminopurine (6-DMAP), cytochalasin B (CyB) and cycloheximide (CHX) on in vitro development of “I” pig somatic cell nuclear transfer embryos. Oocytes after SCNT were activated with 2 mM 6-DMAP; 7.5 µg/ml CyB and 10 µg/ml CHX. The results indicated that the rate of oocytes no lysis in group activated by CHX was significantly lower compared with those in group activated by 6-DAMP and CyB (90.91% and 88.01%, respectively, P < 0,05). The blastocyst formation rate did not differ between group actvated by 6-DAMP and CyB (24.93% vs 24.4%, P > 0.05). Meanwhile the blastocyst formation rate in group activated by CHX was 15.01%, significantly lower than that in group activated by 6-DAMP and CyB (P < 0.05). The average number of cells in the blastocyst in group activated by 6-DAMP and CyB were higher than that in group activated by CHX (47.78, 44.57 vs 39.42, respectively). The use of 6-DMAP and CyB in the activation of pig oocytes after SCNT was more effective than CHX. The results of this study show that for the first time in Vietnam, we have created “I” pig SCNT embryo without zona pellucida with the rate of blastocyst formation from 15.01% to 24.93%.